Community Participation in Forest Conservation as A Forest Fire Mitigation and Adaptation on The Arjuno Mountain - Riza, Sativandi; Fata, Yulia Amirul; Arifin, Syamsul; Hadiwijoyo, Erekso; Hidayatullah, Rifqi Rahmat; Ishaq, Rizki Maulana; Lestari, Nina Dwi; Putra, Aditya Nugraha; Lestariningsih, Iva Dewi; Suprayogo, Didik (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Participatory conservation is an activity to mitigate and adapt to forest and land fires through field farmer school (FFS) activity which forest farmer groups (FFG), non-governmental organizations (NGOs), and academics attend. This research aims to provide an innovative approach to conservation activities with the community, especially on Mount Arjuno, which often experiences forest fires. The results show that local stakeholders and authorities must support community participation in forest conservation. This study shows that FFS (Field Farmer School) activities can facilitate the community in identifying problems and generating ideas for conservation activities through the agroforestry system, mitigation and adaptation of forest and land fires, and edu-ecotourism. Conservation designs and community participation strategic plans are outputs of forest fire mitigation and adaptation activities. The FFS as the methodology used is adequate for knowing what the farmer needs relating to conservation that stakeholders will program. Moreover, generating the conservation activity must be combined with activities to increase the FFG income. So, the FFG will have good welfare.